HUMAN CONDITION IN A GLOBALIZED SOCIETY OF RISKS AS A SOCIAL AND ETHICAL PROBLEM - Yermolenko, A. M. (Anthropological Measurements of Philosophical Research, 2020)
Purpose. The study aims at thematizing social and ethical problems related to the changes of the human condition in the contemporary globalized society of risks. These risks include threats of not only physical destruction of human race, but also transformation of the natural constitution of the human being. The task of achieving this objective also includes comparative analysis of this problem in the classical and contemporary philosophical anthropology. Theoretical basis. Works of the representatives of the contemporary philosophical anthropology, including the methodology of the transcendental anthropology as discursive ethics. Originality. Contrary to the classical philosophical anthropology, which was based on the concept of the human being as "unfinished project of nature", the author suggests a concept of human being as "unfinishable project of history" which poses new requirements to the ethics both on the level of its fundamentals, and on the level of its application. Conclusions. The complex globalized world needs axiological and normative re-orientation of the society based upon universalist macroethics of discourse. This macroethics should aim at Letztbegründung of the moral and ethical imperatives for the future development of society, changes of humanity and its natural constitution.